1995
DOI: 10.1039/p29950000831
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR and FT-IR studies of the interaction between 1,8-bis(dimethylamino)naphthalene and 3,5-dichlorophenol

Abstract: The 'H and 13C NMR spectra of the complex between 1,8-bis(dimethylarnino)naphthalene and 3,5dichlorophenol have been studied at temperatures between 30 "C and -70 "C in CD,Cl, and at different acid to base concentration ratios. At a temperature of -60 "C a splitting of the 'H and 13C signals of DMAN and DMANH+ is observed. The protonation degree deduced from the NMR data and the intensity of the Bohlmann bands are in very good agreement. At a temperature below 8 "C, a splitting (2.6 Hz) of the methyl protons c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…As a measure of such asymmetry, the "proton localization" index, PL, was suggested earlier. 14a It is based on the observation that when a proton is entirely located on the aniline NMe 2 group, as in case of N,N-dimethylanilinium cation, 15 the spin−spin coupling constant 3 J NH,NMe is normally about 5.2 Hz. In the usually symmetric cation 1H + , the NH proton in the NMR time scale equally belongs to two nitrogen atoms, and the value 3 J NH,NMe is halved to ∼2.6 Hz, remaining 5.2 Hz totally.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a measure of such asymmetry, the "proton localization" index, PL, was suggested earlier. 14a It is based on the observation that when a proton is entirely located on the aniline NMe 2 group, as in case of N,N-dimethylanilinium cation, 15 the spin−spin coupling constant 3 J NH,NMe is normally about 5.2 Hz. In the usually symmetric cation 1H + , the NH proton in the NMR time scale equally belongs to two nitrogen atoms, and the value 3 J NH,NMe is halved to ∼2.6 Hz, remaining 5.2 Hz totally.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For asymmetric derivatives of DMAN, both 3 J NH,NMe constants become different but their sum still remains near 5.2 Hz, from which it is easy to calculate the PL. Of course, such calculations may seem rough, but other estimates of the PL, in particular based on the differences between the coupling constants of the NH proton with two 15 N nitrogen atoms, give quite close results. 14b −d As depicted in Table 1, the NH proton in cation 6H + in both CD 3 CN and DMSO-d 6 by 90% resides on the NMe 2 group ( 3 J NH,NMe = 4.7 Hz).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Discovery of the abnormally high basicity of 1,8-bis(dimethylamino)naphthalene ( 1 ), widely known as ‘proton sponge’, has raised a great interest in the nature of intramolecular hydrogen bonding (IHB) of its cation 2 . In dozens of papers such properties of the IHB such as symmetry and geometry, energy, the barrier and mechanism for proton transfer, unusually strong deshielding of the chelated NH proton (δ 18–20 ppm), etc., have been investigated (see reviews for a general survey of the topic). As a result, it was concluded that the IHB strength in 2 after electrostatic and steric destabilization of the free base 1 is, by importance, a second factor contributing to the proton sponge basicity. ,, Due to the unique shortness of the IHB ( r N···N = 2.52–2.57 Å), , the proton sponge cations have also attracted considerable attention for proton transfer modeling in enzymatic reactions…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, IR and 13 C NMR spectroscopy usually unambiguously indicate the place of coordination of the chelate proton and the participation/nonparticipation of the C=O group in H‐bonding in solution and solid phase. Indeed, despite the low value of the chemical shift of the NH proton (10.43 ppm) and its almost 90 % localization on the dimethylamino group (judging by 3 J NH,NMe =4.5 Hz), [28,29] it is the amide nitrogen atom that participates in chelation, as evidenced by the distinct downfield shift of the carbonyl group signal in the carbon spectrum from 168 to 175 ppm on going from 14 to 14 ⋅ HBF 4 , respectively [25,27] …”
Section: Resultsmentioning
confidence: 99%